PEMBANGUNAN NILAI MORAL DAN KARAKTER MAHASISWA MELALUI PENERAPAN MODEL PROJECT CITIZEN DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI UNIVERSITAS MUHAMMDIYAH PURWOKERTO - Eko Priyanto; Nadarajan A/L Thambu (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The existence of Civic Education(PKn) Course in the Higher Education curriculum is a compulsory subject that must be taken and passed by every student, so it is known as the General Compulsory Course (MKWU). Moreover, due to its mission on developing students' personalities, Civic Education is also known as the Personality Development Course (MKPK). However, the problem that still arises is the attitude and behavior of some students who violate moral values and character, such as cheating during exams, plagiarizing other people's work in doing assignments, drinking alcohol, doing immoral actions or promiscuity, brawling among students or groups of students, skipping lectures beyond the tolerance. In addition, another problem commonly faced is the non-optimal learning process for Civic Education which is known from the lack of students' involvement in the learning process. The implementation of the Citizen Project Model as an effort to solve problems in Civic Education learning could make students understand and behave in accordance with moral values and character as citizens. Furthermore, this model could also make students active, creative, collaborative, disciplined, and build good relations with the community and government officials. This study aims to examine the Project Citizen model in building students' moral values and character at the Universitas Muhammadiyah Purwokerto (UMP). This research was carried out with a qualitative approach using a Participatory Action Research (PAR) design. The students were involved in each stage of Project Citizen in three participatory action cycles. The data collection technique used interviews, observations, video recordings, and documents. The data analysis used theme analysis. The study results prove that the stages of the project citizen model can build UMP students' moral values and character. UMP students' moral values and character are described in 8 themes, including rationality, justice, honesty, kindness, prosocial behavior/doing good to others, the character of citizens, braveness, and motivation to be an open and independent person